Molecular Imaging of Myocardial Fibroblast Activation in Patients with Advanced Aortic Stenosis Before Transcatheter Aortic Valve Replacement: A Pilot Study - Diekmann, Johanna; Neuser, Jonas; Röhrich, Manuel; Derlin, Thorsten; Zwadlo, Carolin; Koenig, Tobias; Weiberg, Desiree; Jäckle, Felix; Kempf, Tibor; Ross, Tobias L.; Tillmanns, Jochen; Thackeray, James T.; et al. (Journal of Nuclear Medicine, 2023)
Using multimodal imaging, we investigated the extent and functional correlates of myocardial fibroblast activation in patients with aortic stenosis (AS) scheduled for transcatheter aortic valve replacement (TAVR). AS may cause myocardial fibrosis, which is associated with disease progression and may limit response to TAVR. Novel radiopharmaceuticals identify upregulation of fibroblast activation protein (FAP) as a cellular substrate of cardiac profibrotic activity. Twenty-three AS patients underwent Ga-FAP inhibitor 46 ( Ga-FAPI) PET, cardiac MRI, and echocardiography within 1-3 d before TAVR. Imaging parameters were correlated and then were integrated with clinical and blood biomarkers. Control cohorts of subjects without a history of cardiac disease and with ( = 5) and without ( = 9) arterial hypertension were compared with matched AS subgroups. Myocardial FAP volume varied significantly among AS subjects (range, 1.54-138 cm , mean ± SD, 42.2 ± 35.6 cm ) and was significantly higher than in controls with (7.42 ± 8.56 cm , = 0.007) and without (2.90 ± 6.67 cm ; < 0.001) hypertension. FAP volume correlated with N-terminal prohormone of brain natriuretic peptide ( = 0.58, = 0.005), left ventricular ejection fraction ( = -0.58, = 0.02), mass ( = 0.47, = 0.03), and global longitudinal strain ( = 0.55, = 0.01) but not with cardiac MRI T1 (spin-lattice relaxation time) and extracellular volume ( = not statistically significant). In-hospital improvement in left ventricular ejection fraction after TAVR correlated with pre-TAVR FAP volume ( = 0.440, = 0.035), N-terminal prohormone of brain natriuretic peptide, and strain but not with other imaging parameters. FAP-targeted PET identifies varying degrees of left ventricular fibroblast activation in TAVR candidates with advanced AS. Ga-FAPI signal does not match other imaging parameters, generating the hypothesis that it may become useful as a tool for personalized selection of optimal TAVR candidates.